2020
DOI: 10.3390/jmse8110901
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Morphodynamics for Beach Intertidal Systems in the North Sea: A Space-Time Stochastic Approach

Abstract: The ability to accurately predict beach morphodynamics is of primary interest for coastal scientists and managers. With this goal in mind, a stochastic model of a sandy macrotidal barred beach is developed that is based on cross-shore elevation profiles. Intertidal elevation was monitored from monthly to annually for 19 years through Real Time Kinematics-GPS (RTK-GPS) and LiDAR surveys, and monthly during two years with an RTK-GPS. In addition, during two campaigns of about two weeks, intensive surveys on a da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Nevertheless, the complete destruction of intertidal bars has never been observed anywhere. At Groenendijk, the bars were also observed on aerial photographs and field measurements back to the 1950s [16,17] and annually from 1990 to the present [13,18]. This is evidence that bars are permanent features of the intertidal beach along Groenendijk and not only on a time scale of years but decades.…”
Section: Temporal and Spatial Variability In Bar Morphologymentioning
confidence: 95%
See 1 more Smart Citation
“…Nevertheless, the complete destruction of intertidal bars has never been observed anywhere. At Groenendijk, the bars were also observed on aerial photographs and field measurements back to the 1950s [16,17] and annually from 1990 to the present [13,18]. This is evidence that bars are permanent features of the intertidal beach along Groenendijk and not only on a time scale of years but decades.…”
Section: Temporal and Spatial Variability In Bar Morphologymentioning
confidence: 95%
“…Recently, ref. [18] have found that the dissimilitude between elevations measured at the same position on a profile at Groenendijk was about 25% and 90% for measurements separated by a time lag of one month and three years, respectively. Thus, the profile elevations become uncorrelated for a time lag exceeding a few years.…”
Section: Tidal Level and Bar Morphologymentioning
confidence: 99%
“…It could be an important factor in deciding which beach sites the coastal managers should develop. There are different techniques and approaches used for predicting beach changes and beach nourishment requirements; from simpler techniques such as linear least squares to more sophisticated models such as stochastic approaches, and finally machine learning techniques [4][5][6][7]. Many models include on longshore and cross shore transport for beach change prediction, as well as equilibrium beach profile expressions [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The third published paper is entitled "Predicting Morphodynamics for Beach Intertidal Systems in the North Sea: A Space-Time Stochastic Approach" by Bogaert et al [3]. The authors developed a stochastic model of a macrotidal sandy-barred beach based on crossshore elevation profiles.…”
mentioning
confidence: 99%